The challenge of supporting networked personal inquiry learning across contexts - Scanlon, Eileen; Kerawalla, Lucinda; Gaved, Mark; Jones, Ann; Collins, Trevor; Mulholland, Paul; Blake, Canan; Petrou, Marilena; Littleton, Karen (Proceedings of the International Conference on Networked Learning, 2010)
Supporting learning across different contexts can be challenging. Defining formal, informal and non-formal learning is the subject of continuing debate as each can be difficult to describe. We report on a study that evaluated the effectiveness of a Personal Inquiry toolkit on supporting personal inquiries into the sustainability of the food cycle, carried out across the contexts of home and an after school club in a UK secondary school. The toolkit consisted of a web-based Sustainability Investigator that could be accessed from any location, together with a selection of data-gathering tools such as environmental sensors (e.g. temperature probes) and cameras. It was designed to support students through the process of carrying out inquiries within the club and between the club and their home. Our main focus here is on describing how the Sustainability Investigator supported students' inquiries that were conceived and designed within the club and conducted at home. The 30 students (aged 12-14 years) chose to investigate home food storage, packaging and preservation. Our focus is on exploring the nature of the semi-formal club context and how this mediated students' use of the Sustainability Investigator. Analysis of our field notes, log files of students' use of the Sustainability Investigator, together with video and audio recordings of club sessions and interviews with teachers and pupils, suggest that while the pupils' use of the tool kit across contexts was sporadic and varied between students, they successfully completed personally relevant inquiries and developed positive attitudes to the process .This was different to the predictable, sustained and consistent use of the tool kit identified in our previous studies when the students used it (again successfully) to support their inquiries in a formal classroom setting (e.g. Scanlon et al. 2009). Three main features of the school club context that mediated the ways in which the Sustainability Investigator was used by the students across contexts were: 1) the students' aims and priorities, 2) affordances and constraints of the technology, and 3) institutional priorities. We use this example of a study of learning across contexts to suggest implications of the work for the potential of a Personal Inquiry toolkit to support learning across the life course.